Peer Feedback of L2 Writing Class in Blended Learning Context - Devian Try Gustary; Bayu Andika Prasatyo; Sulhizah Wulan Sari (Universitas Cokroaminoto Palopo, 2022)
This paper reports the finding of a study scrutinizing to what extent peer feedback in blended learning context improves students’ writing ability a well as how EFL learner perceive an online peer feedback on writing in blended learning context. The study utilized a descriptive qualitative method with instrument of observation, document analysis and questionnaires. The results show that the students writing ability have improved after the students received feedback from peers and incorporated those feedbacks to their final draft. The online peer feedback fostered students’ writing skills in terms of mechanic, content, organization and structures. Students’ perception of online peer feedback using Edmodo were also positive in terms of usefulness, easiness, and interest. The students also responded that this activity was very timesaving since the blended learning model facilitates the students to maximize the amount of time to engage in the writing process.